2002
DOI: 10.1111/j.1095-8649.2002.tb02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiaminase activity of gastrointestinal contents of salmon and herring from the Baltic Sea

Abstract: Potential thiaminase activity of Baltic herring Clupea harengus ranged from 0 to c. 55 nmol g 1 min 1 while potential thiaminase activity in Baltic salmon Salmo salar gastrointestinal (GI) contents ranged from 7 to c. 60 nmol g 1 min 1 . About 30% of the Baltic herring analysed had a potential thiaminase activity equivalent to Baltic salmon GI contents. The results are consistent with the hypothesis that thiaminase in the forage fish of Baltic salmon may be an important link in the aetiology of the thiamine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Despite the positive correlation found between the M74 prevalence and the sprat stock biomass, the proportion of sprat appeared to constitute a smaller part of the diet of Baltic salmon in 1994–1997 when the prevalence of M74 mortality was high compared to the period 1959–1962 when M74 was not observed (Hansson et al , 2001). These observations confirm the conclusions based on present and previous results (Wistbacka et al , 2002) that Baltic herring, with high thiaminase activity, rather than sprat, is the immediate causal factor for the M74 syndrome in Baltic salmon.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite the positive correlation found between the M74 prevalence and the sprat stock biomass, the proportion of sprat appeared to constitute a smaller part of the diet of Baltic salmon in 1994–1997 when the prevalence of M74 mortality was high compared to the period 1959–1962 when M74 was not observed (Hansson et al , 2001). These observations confirm the conclusions based on present and previous results (Wistbacka et al , 2002) that Baltic herring, with high thiaminase activity, rather than sprat, is the immediate causal factor for the M74 syndrome in Baltic salmon.…”
Section: Discussionsupporting
confidence: 93%
“…Baltic herring Clupea harengus membras L. and sprat Sprattus sprattus (L.), the major prey species in the diet of Baltic salmon (Karlsson et al , 1999), contain thiaminase (Melnick et al , 1945; Kuusi, 1963; Hirn & Pekkanen, 1975; Anglesea & Jackson, 1985; Soivio & Hartikainen, 1999; Wistbacka et al , 2002). Unlike North America where non‐native prey species appear responsible for the deficiency, in Baltic salmon the native clupeids, Baltic herring and sprat, appear responsible, even though they appear to have coexisted for several millennia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiamine is of particular interest in fisheries research because of the link between poor offspring survival and low thiamine concentrations in females and their ova, particularly in salmonine populations of the Laurentian Great Lakes basin (Fitzsimons et al , 1999, 2007) and the Baltic Sea (Amcoff et al , 1999). Briefly, the availability of maternal thiamine for deposition in eggs is believed to be compromised by the presence of thiaminase in the intestinal flora of prey fishes in these waters (Ketola et al , 2000; Honeyfield et al , 2002; Wistbacka et al , 2002; Tillitt et al , 2005). Oxidative stress occurs concurrently with thiamine deficiency in Baltic Sea fishes (Pickova et al , 1998; Vuori et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sebastes spp., Hexagrammidae, and Engraulis mordax). Previous studies with alewife, rainbow smelt, and Baltic herring Clupea harengus found thiaminase activity to be highly variable (Wistbacka et al 2002;Tillitt et al 2005;Honeyfi eld et al 2012). More importantly, Wistbacka and Bylund (2008) suggested that Baltic salmon with a high incidence of thiamine defi ciency (referred to as M74) targeted herring with higher thiaminase activity.…”
Section: Discussionmentioning
confidence: 99%